Fashioning The Gays: A Representation Study on the Gay Protagonists in the 2000s Gay-themed American TV Series - Rudy Rudy; Galant Nanta Adhitya (Universitas Sanata Dharma, 2022)
This study focuses on the relationship between fashion and the gay community by observing the 2000s American TV series with gay characters as the protagonists. It intends to explain the way fashion is portrayed and its significance for gay culture. It can contribute to theory enrichment in cultural, literary and media studies. It would also increase people’s knowledge about fashion in and for the gay culture. This research incorporated the main data in the form of dialogues as well as pictures of scenes showing fashion worn by the gay characters obtained from Will Grace (1998-2006), Queer as Folk (2000-2005), Six Feet Under (2001-2005), and Some of My Best Friends (2001). By applying Hall’s representation theory to analyze the data, this study discovers that the gay protagonists in the 2000s gay-themed American TV series are portrayed as fashionable people, who think of fashion as their pride. However, the fashion used in portraying gay characters has shifted from the effeminate looks that are mostly composed of women’s clothes. Instead, they are still seen concerning with their appearance, but their exploration of fashion is sticking to men’s clothes. This portrayal has two essential significances for the gay community. It affirms the modish of their identity, while at the same time refusing the feminine stereotype.